A new look at the cognitive neuroscience of video game play. Issue 1 (13th January 2020) - Dale, Gillian; Joessel, Augustin; Bavelier, Daphne; Green, C. Shawn
Abstract: A growing body of literature has investigated the effects of playing video games on brain function and behavior. One key takeaway from this literature has been that not all entertainment video games are created equal with respect to their effects on cognitive functioning. The majority of the research to date has contrasted the cognitive impact of playing first‐ or third‐person shooter games (together dubbed "action video games") against the effects of playing other game types. Indeed, when the research began in the late 1990s, action video games placed a load upon the perceptual, attentional, and cognitive systems in a manner not seen in other video games. However, the video game industry has shifted dramatically over the intervening years. In particular, first‐ and third‐person shooter games are no longer unique in the extent to which they load upon cognitive abilities. Instead, a host of other game genres appear to place similar degrees of load upon these systems. This state of affairs calls for a paradigm shift in the way that the cognitive neuroscience field examines the impact of video game play on cognitive skills and their neural mediators—a shift that is only just now slowly occurring.